IN VITRO HYPOGLYCEMIC ACTIVITY OF CRUDE ETHANOLIC LEAF EXTRACT OF COLDENIA PROCUMBENS - PRADEEP, MALAVIKA; Gayathri .R,; V.Vishnu Priya, (International Journal of Psychosocial Rehabilitation, 2020)
To analyse and estimate the hypoglycemic activity of ethanolic leaf extract of Coldenia procumbensColdenia procumbens was weighed and crushed in pestle and mortar and 50% of ethanolic extract was prepared by solvent extraction method hypoglycemic activity of coldenia procumbens was evaluated.From the study it is evident that ethanolic extract of coldenia procumbens possess hypoglycemic activityThe extract can be further purified and analysed for it’s hypoglycemic activity in invivo studies.